Local complications of vein canulation - Parma, Dante; Saéz, Hugo (Cirugía del Uruguay, 1978)
Case material comprises 50 observations of patients in one hospital, in whom veins had to be exposed, for canulation. From the study of these cases the authors conclude that complications are due, in 80 % of cases, to iatrogenic causes. It woult seem that this procedure is resorted to excessively.